The logistics and supply chain toolkit over 100 tools and guides for supply chain, transport, warehousing and inventory management - Richards, Gwynne; Grinsted, Susan (Kogan Page, 2016)
Providing practical and applicable solutions to some of the most frequently encountered problems in the industry, this updated second edition of The Logistics and Supply Chain Toolkit offers revised toolsthat reflect the latest innovations in technologies and processes. The book also includes new tools on calculating stock-holding cost, calculating ordering cost, managing slow-moving inventories, and new